Kualitas Pelaporan Keuangan : Peran Keahlian Industri Pada Komite Audit - Ashifa Amalia (Universitas Muhammadiyah Malang, 2022)
This study aims to look at the role of audit committee’s industry expertise on the quality of corporate financial reporting. By using the purposive sampling method for all companies listed on the Indonesia Stock Exchange (IDX) in the period 2016 to 2019, the final sample size was 584 observations. The data needed is obtained from the company's financial reports, the Osiris database, the company's website, the Bloomberg website, and LinkedIn. By testing descriptive statistics and multiple linear regression using STATA 14.0 software, this study shows that when a company's audit committee has only one of industry and accounting or financial expertise, the supervisory role of financial reporting tends to be less effective. On the other hand, when the company's audit committee team has both expertise, the supervisory role of the audit committee increases so that the quality of the company's financial reporting also increases. These results imply that the audit committee's industry expertise is useful for increasing the effectiveness of financial reporting supervision so that this expertise needs to be considered as a factor in selecting an audit committee.